2014
DOI: 10.1016/j.lfs.2014.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of DNA methylation in UVB- and DMBA/TPA-induced mouse skin cancer models

Abstract: Aims Ultraviolet irradiation and carcinogens have been reported to induce epigenetic alterations, which potentially contribute to the development of skin cancer. We aimed to study the genome-wide DNA methylation profiles of skin cancers induced by ultraviolet B (UVB) irradiation and 7,12-dimethylbenz(a)anthracene (DMBA)/12-O-tetradecanoylphorbol-1,3-acetate (TPA). Main methods Methylated DNA immunoprecipitation (MeDIP) followed by next-generation sequencing was utilized to ascertain the DNA methylation profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 35 publications
2
21
0
1
Order By: Relevance
“…MeDIP was performed using a MagMedIP kit (Diagenode, Denville, NJ, USA) as previously described [ 63 ]. Briefly, immunoprecipitations were performed using a monoclonal antibody against 5-methylcytidine (Diagenode, Denville, NJ, USA) to separate the methylated DNA fragments from the unmethylated fragments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MeDIP was performed using a MagMedIP kit (Diagenode, Denville, NJ, USA) as previously described [ 63 ]. Briefly, immunoprecipitations were performed using a monoclonal antibody against 5-methylcytidine (Diagenode, Denville, NJ, USA) to separate the methylated DNA fragments from the unmethylated fragments.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, the samples were subjected to Illumina next-generation sequencing (Otogenetics Corporation, Norcross, GA, USA). After downloading the BAM files for analysis, MeDIP alignments were compared with control samples using Cuffdiff 2.0.2 as previously described [ 64 , 63 ]. To judge the quantitative enrichment in MeDIP samples versus control samples in Cuffdiff, the overlapping regions of sequence alignment common to the MeDIP and control samples were used.…”
Section: Methodsmentioning
confidence: 99%
“…For example, drugs that target histone deacetylases (HDACs) and DNA methyltransferase (DNMT) inhibitors have been approved by the FDA as chemotherapeutics, although their toxicity limits their applications (12, 13). Aberrant epigenetic alterations have been observed in the initiation and progression of skin cancers (1417). Certain dietary phytochemicals that possess chemopreventive effects have been reported to prevent cancer by targeting epigenetic modifications (18, 19).…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation on 5-cytosine (5-mC) and covalent modifications to histone tails are the major mechanisms that maintain DNA stability and control gene transcription at the epigenetic level. Recent publications from our group and others have identified that aberrant DNA methylation is associated with altered gene expression in cancer models in vitro and in vivo [1, 2]. In addition, loss of 5-hydroxymethylcytosine (5-hmC) and ten-eleven translocation 2 (TET2) protein expression has been reported in malignant melanoma [3].…”
Section: Introductionmentioning
confidence: 99%